Improving effectiveness of material planning of supply chain management using business process modelling - Tan, Ying Yan (2024)
supply chain management frameworks using the Business Process Model and Notation (BPMN). Material planning plays a critical role in supply chain operations, impacting production schedules, inventory levels, and operational costs significantly. However, traditional material planning processes often need more standardisation and communication barriers due to the use of conventional diagramming methods such as flowcharts. BPMN offers a better alternative by providing a standardised graphical representation of business processes and a structured and visual approach to modelling and analysing workflows. The expected outcomes include increased process visibility, standardised operations, enhanced communication, efficient workflows, improved decision-making, cost reduction, and improved adaptability.